In silico single cell dynamics of hepatitis B virus infection and clearance. (7th February 2015) - Murray, John M.; Goyal, Ashish
Abstract: The progression of acute hepatitis B virus (HBV) to chronic infection or clearance is highly dependent on the host immune response composed of cytolytic (CTL) and non-cytolytic (non-CTL) effects. Cytolytic processes induce hepatocyte killing while non-CTL processes inhibit intracellular replication. Both effects are widely recognized and accepted. However, there are uncertainties about the assistance provided by either the loss of covalently circular closed DNA (cccDNA) during cell proliferation or the emergence of refractory cells to immune mediated clearance. We developed an agent-based mathematical model and tested the relative roles of different mechanisms of the immune system in the clearance of acute HBV infection. HBV viremia clearance time and hepatocyte turnover (HT) were used as the two major criteria in determining reasonable outcomes. Modelling results in 90% of cells containing between 1 and 17 cccDNA copies and normally distributed at the peak of infection. Variations in p36 levels, responsible for determining export of virions or recirculation to amplify cccDNA numbers, have a much greater impact on mean cccDNA level/cell at peak viremia than virus infectivity and cccDNA half-life. A strong CTL effect alone failed to clear infection with HT≈10. Acute infection clearance was possible with combined CTL and non-CTL effects along with complete loss of intracellular viral components during cell proliferation resulting in the desired range of HT (0.7–1). The emergence of cells refractory to infection can reduce HT by up to 90%. However their impact was less effective than complete loss of intracellular viral components during cell proliferation. Conclusion: the existence of refractory cells is not necessary when there is complete loss of intracellular quantities during cell proliferation but is essential with only partial clearance. Highlights: Cell proliferation plays an important role in HBV infection clearance. The complete loss of intracellular components during cell proliferation is vital for infection clearance with minimal hepatocyte death. Refractory cells are essential if there is only partial loss during cell proliferation. Targeting intracellular p36 levels may provide an effective therapy for HBV.